2020
DOI: 10.1017/jfm.2020.835
|View full text |Cite
|
Sign up to set email alerts
|

Rapid spectral evolution of steep surface wave groups with directional spreading

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 86 publications
(192 reference statements)
3
12
1
Order By: Relevance
“…This observation is consistent with Trulsen & Dysthe (1997) and the rapid energy transfer reported in Barratt et al. (2021). Barratt et al.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…This observation is consistent with Trulsen & Dysthe (1997) and the rapid energy transfer reported in Barratt et al. (2021). Barratt et al.…”
Section: Resultssupporting
confidence: 93%
“…For the relevant cases computed in this section, we used and m which is typical of the North Sea (Barratt et al. 2021). Using the spectra described by (6.1 a , b ), linear elevation at is given as input by with for unidirectional waves, where denotes the dimensionless steepness of a wave group at linear focus; and denote the evenly spaced discrete wavenumbers and the total number chosen for numerical implementations, respectively; the subscript ‘’ denotes the position or time for the wave group at linear focus; denotes the wave phase at linear focus; for multidirectional waves, with where and denote the evenly spaced discrete wave directions in the range of and the total number chosen for numerical implementations, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only the parameters of the MNLS carrier wave and the dimensionless depth (k pd ) of the domain are varied. Barratt et al (2021) showed that the absence of the spectral tail can result in augmented wave-wave interactions. Thus, the spectra used in this study represent a conservative test of the MNLS equation, since more realistic spectra are likely to result in weaker wave-wave interactions than those observed in this investigation.…”
Section: Initial Conditionsmentioning
confidence: 99%
“…For the MNLS simulations, removal of the bound harmonics is not necessary and ϕ 0 is set to zero, causing linear focus to occur at (x = 0, y = 0, t/T 0 = 0). For the OceanWave3D simulations, each simulation is repeated with ϕ 0 values of 0 • , 90 • , 180 • and 270 • to remove the bound harmonics with four-phase separation, as used by Barratt et al (2021). The angular frequency of each component (ω i ) is calculated from the arbitrary-depth linear dispersion relationship, ω i = √ gk i tanh (k i d), allowing the initial conditions to be calculated at t/T 0 = −15.…”
Section: Initial Conditionsmentioning
confidence: 99%